2013
DOI: 10.1016/j.lwt.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Production of edible mushroom and degradation of antinutritional factors in jatropha biodiesel residues

Abstract: a b s t r a c tThe elimination of antinutritional factors of the Jatropha curcas L. seed cake is important for decreasing environmental damage and adding economic value to this residue of the biodiesel industry. In this study, we analyzed the ability of Pleurotus ostreatus to degrade antinutritional factors and produce edible mushrooms using different proportions of the J. curcas seed cake as substrate. After 60 d of incubation at 25 C, we observed 95% phytic acid and 85% tannins reductions, and high mushrooms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…However, hydrogen was only generated when the cotton-seed cake was pretreated with NaOH (10 %) (Panagiotopoulos et al 2013). In a different approach, seed cakes have been used in solid-state fermentation to produce edible fungus and enzymes (Veerabhadrappa et al 2014;da Luz et al 2013). da Luz et al (2013) described the production of the edible fungus Pleurotus ostreatus from jatropha seed cake; this fungal strain degraded the antinutritional factors in the jatropha seed cake (da Luz et al 2013).…”
Section: Treatment Of Other Biodiesel Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hydrogen was only generated when the cotton-seed cake was pretreated with NaOH (10 %) (Panagiotopoulos et al 2013). In a different approach, seed cakes have been used in solid-state fermentation to produce edible fungus and enzymes (Veerabhadrappa et al 2014;da Luz et al 2013). da Luz et al (2013) described the production of the edible fungus Pleurotus ostreatus from jatropha seed cake; this fungal strain degraded the antinutritional factors in the jatropha seed cake (da Luz et al 2013).…”
Section: Treatment Of Other Biodiesel Residuesmentioning
confidence: 99%
“…In a different approach, seed cakes have been used in solid-state fermentation to produce edible fungus and enzymes (Veerabhadrappa et al 2014;da Luz et al 2013). da Luz et al (2013) described the production of the edible fungus Pleurotus ostreatus from jatropha seed cake; this fungal strain degraded the antinutritional factors in the jatropha seed cake (da Luz et al 2013). Similarly, Veerabhadrappa et al (2014) reported proteases and lipases from Aspergillus versicolor CJS-98 in the solid-state fermentation of jatropha seed cake.…”
Section: Treatment Of Other Biodiesel Residuesmentioning
confidence: 99%
“…Jc has been used as a substrate for white-rot fungal growth (de Barros et al, 2011;Kasuya et al, 2012;da Luz et al, 2013;Da Luz et al, 2014). However, previous studies focused on the degradation of phorbol ester to improve the usefulness of this material.…”
Section: Troductionmentioning
confidence: 99%
“…The substrate was then innoculated using fungi grown in rice and incubated for 45 days at 25°C. This incubation time was determined based on a previous study (da Luz et al, 2013). Three grams sample from each flask were used to determine the pH, as well as ergosterol, lignin and cellulose/hemicellulose levels.…”
Section: Substrate Composition and Growth Conditionsmentioning
confidence: 99%
“…Curcin and the antinutritional factors can be degraded by thermal or biological treatments (Aregheore et al, 2003;Kasuya et al, 2012;Rehman and Shah, 2005). da Luz et al (2013) showed the degradation of antinutricional factors by Pleurotus ostreatus.…”
Section: Introductionmentioning
confidence: 99%